The Impact of TikTok on Combating and Filtering Hoax News: A Mixed-Methods Study - Fransisco Ruak (IHSA Institute, 2023)
In an era marked by the rapid dissemination of information on social media, the prevalence of hoax news has emerged as a formidable challenge, affecting the credibility of digital platforms and the veracity of information. This research investigates the role of TikTok, a prominent short-form video-sharing platform, in curbing and filtering hoax news. Utilizing a mixed-methods approach, our study combines content analysis, surveys, user interviews, and analysis of fact-checking reports to comprehensively assess TikTok's influence. Initial findings from content analysis revealed a significant presence of hoax news on TikTok, encompassing false claims, conspiracy theories, and deceptive narratives. However, a striking observation emerged over the course of a year, as a noticeable reduction in the prevalence of hoax news content was noted, suggesting TikTok's efforts to combat misinformation. Survey data shed light on user awareness, behaviors, and perceptions of hoax news on TikTok, highlighting varying levels of concern and trust in the platform's content moderation mechanisms. Qualitative insights gathered from user interviews and focus groups offered diverse perspectives, ranging from appreciation for TikTok's initiatives to skepticism about its effectiveness. The analysis of fact-checking reports underscored TikTok's proactive approach in addressing hoax news, with a significant proportion of reports debunking such content. These findings collectively demonstrate TikTok's influence on curbing hoax news. In conclusion, TikTok plays a significant role in mitigating the spread of hoax news, as evidenced by the reduction in its prevalence and the platform's commitment to fact-checking. User attitudes, behaviors, and trust remain pivotal in shaping the dynamics of misinformation. This research contributes to our understanding of the complex interplay between social media platforms and misinformation, emphasizing the need for collaborative efforts among platforms, users, and policymakers to foster a trustworthy digital environment